Adsorption properties of basil (Ocimum basilicum L.) seed gum - Osano, Joenalyn P. (USM R & D Journal, 2010)
The study investigated the adsorption properties of a novel polysaccharide extracted from the seeds of Basil (Ocimum basilicum L.). The effect of protein contents on the surface activity of the gum was also determined. Different Basil Seed Gum (BSG) preparations based on their purification processes were termed crude BSG, purified BSG, and protein-free BSG. Varying concentrations (0.1-1% wt/wt) of these gum solutions were prepared and hydrated overnight at room temperature. The adsorption properties of BSG were characterised in terms of surface/interfacial tensions. Results revealed that all the gum preparations (crude purified, and protein-free)exhibited the ability to reduce the surface tension of pure water. Increasing the gum concentration substantially reduced the surface tension of the air and water interface to as low as 47.8 mN/m for crude BSG, 51.3 mN/m for purified BSG and 52.5mN/m for protein-free BSG, at 1% (wt/wt) gum concentration. Similarly, the interfacial tension at the oil/water interface was significantly lowered in all gum preparations. With the increase in gum concentration, the interfacial tension was substantially reduced: 12.6 mN/m for crude BSG, 22.3 mN/m for purified BSG and 27.7 mN.m for protein-free BSG all at 1% (wt/wt) gum concentration. Surface/interfacial tension measurements confirmed the adsorption of BSG at the oil-water interfaces. All gum preparations (crude, purified, and protein-free) exhibited an ability to lower the tensions at the interface. However, purification of the gum reduced its adsorption activity, indicating that (i) protein played an important role in gum adsorption, but was not an absolute driving force for adsorption and (ii) gum itself becomes altered by the purification process.